Characteristics of time-transgressive Holocene Optimum in the East Asian monsoon region - Weihe, Ren; Yi, Guitian (Earth Sciences Research Journal, 2019)
The Holocene Optimum (HO) defines a relatively warm and wet period during the Holocene, the initial and termination ages of which have been extensively reported for East Asia; however, debates still focus on underlying spatial and temporal patterns. Here, latest paleoclimate records from the East Asian monsoon region and arid central Asia are synthesized to evaluate the spatial and temporal patterns of the HO. The results of this synthesis indicate that the latitude and both the initial and termination ages of the HO follow a strong relationship, which is an expansion and northward retreat of the HO except for records around the Tibetan Plateau and several other highlands. Both the HO and technological development are also suggested to have shaped the historic boom of the Neolithic human demography. This study provides a window toward an improved understanding of the characteristics of time-transgressive HO and allows to make predictions for the initial and termination ages of the HO at different geographical locations of the East Asian monsoon region.